HomeTown Restaurant - Abdul Sanny, Abdul Suhaifi; Awang Fauzi, Muhammad Yusof; Mazlan, Shahrin Mazwan; Masri, Mohd Ashraaf (2015)
HomeTown Restaurant is a fast food concept restaurant located in the midst of bustling city of Kota Kinabalu. We can be loosely described as a fast food restaurant that serves local food where customers only need to place their order at the cashier and it will be served and is ready eat. HomeTown Restaurant will hold true to its vision of being a fast food concept restaurant that focus on serving local food in order to become a favorite spot to Kota Kinabalu natives. HomeTown Restaurant also hopes to become a destination for the thousands of tourists, both Malaysian and foreign, who visit Kota Kinabalu every year. There are varieties of restaurants all over Kota Kinabalu nowadays that offers all type of foods as well as services which fulfill the needs of all range of customers. However, most of the restaurants offer the same thing with same service and this became a catalyst for us to establish a restaurant that stands out among the rest. We came up with an idea to open up a fast food concept restaurant focus on serving Malaysian local food. The target markets are the working Sabahan that are on the go, but would still prefer to eat the ever so loved local cuisines without having to sit still on a table waiting for it to be prepared. The concept came with the idea that Malaysian cuisine will be able to be served as a fast food that stands in line with the other fast food restaurants, without sacrificing the authenticity and the quality of Malaysian food that locals came to know and love for generations.